2017
DOI: 10.1111/vcp.12469
|View full text |Cite
|
Sign up to set email alerts
|

Bartonella henselae in canine cavitary effusions: prevalence, identification, and clinical associations

Abstract: Viable B henselae organisms occur in pleural and peritoneal effusions of dogs; the clinical relevance of which remains unclear and may represent opportunistic infection. Associations found in this study included seasonal variation, age, breed, and site of effusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Specialized culture techniques including lysis centrifugation, cell culture isolation and growth enrichment in insect biochemical composition growth media are the “gold standard” for confirmation of Bartonella infection. Optimal samples for microbiological culture include blood, cerebrospinal fluid [ 138 ], joint fluid [ 81 ], pathological effusions [ 138 ] and tissue biopsies [ 139 ]. In reservoir-adapted hosts such as rodents and cats and infrequently in accidental hosts (sick dogs or humans), Bartonella spp.…”
Section: Diagnosis and Identification Methodsmentioning
confidence: 99%
“…Specialized culture techniques including lysis centrifugation, cell culture isolation and growth enrichment in insect biochemical composition growth media are the “gold standard” for confirmation of Bartonella infection. Optimal samples for microbiological culture include blood, cerebrospinal fluid [ 138 ], joint fluid [ 81 ], pathological effusions [ 138 ] and tissue biopsies [ 139 ]. In reservoir-adapted hosts such as rodents and cats and infrequently in accidental hosts (sick dogs or humans), Bartonella spp.…”
Section: Diagnosis and Identification Methodsmentioning
confidence: 99%
“…, Weeden et al . ). Myocardial damage has also been found in dogs with ehrlichiosis, but PE is not commonly reported (Diniz et al .…”
Section: Discussionmentioning
confidence: 97%
“…This phenomenon was also observed in canine, as reported by Cherry N. et al in 2009 [ 20 ]. Interestingly, a canine study led by Weeden A. et al indicated positive B. henselae DNA in pleural and peritoneal effusion while pericardial effusion showed negative results [ 21 ]. In our case, the recurrence of localized mass and subsequent pleural effusion was parallel to COVID infection, possibly due to disrupted immune response.…”
Section: Discussionmentioning
confidence: 99%